The physiological functions of human peroxisomes - Wanders, Ronald J A (2023)
Peroxisomes are subcellular organelles that play a central role in human physiology by catalyzing a range of unique metabolic functions. The importance of peroxisomes for human health is exemplified by the existence of a group of usually severe diseases caused by an impairment in one or more peroxisomal functions. Among others these include the Zellweger spectrum disorders, X-linked adrenoleukodystrophy, and Refsum disease. To fulfill their role in metabolism, peroxisomes require continued interaction with other subcellular organelles including lipid droplets, lysosomes, the endoplasmic reticulum, and mitochondria. In recent years it has become clear that the metabolic alliance between peroxisomes and other organelles requires the active participation of tethering proteins to bring the organelles physically closer together, thereby achieving efficient transfer of metabolites. This review intends to describe the current state of knowledge about the metabolic role of peroxisomes in humans, with particular emphasis on the metabolic partnership between peroxisomes and other organelles and the consequences of genetic defects in these processes. We also describe the biogenesis of peroxisomes and the consequences of the multiple genetic defects therein. In addition, we discuss the functional role of peroxisomes in different organs and tissues and include relevant information derived from model systems, notably peroxisomal mouse models. Finally, we pay particular attention to a hitherto underrated role of peroxisomes in viral infections.